2020
DOI: 10.2196/15801
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability of Text Messaging to Help African American Women Manage Anxiety and Depression: Cross-Sectional Survey Study

Abstract: Background The rates of mental illness among African American women are comparable with the general population; however, they significantly underutilize mental health services compared with their white counterparts. Previous studies revealed that interventions delivered via text messaging are effective and can be used to increase access to services and resources. More insight into whether or not this modality is acceptable for use to deliver mental health care to help African American women manage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…This study adds to the literature by providing insight into the attitudes of African American women toward seeking mental health services to manage anxiety and depression and the acceptability of using text messaging to communicate with a professional to receive help for managing anxiety and depression. Although the use of text messaging was not highly endorsed by African American women as an acceptable mode to converse with a professional (<50% endorsed), our prior work found that mobile video calls were viewed favorably by the majority of respondents (>70% endorsed) [22]. Concerns around privacy, confidentiality, and the impersonal feel of communicating about sensitive issues via text messages must be addressed for successful participation in text message-based interventions among this population.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This study adds to the literature by providing insight into the attitudes of African American women toward seeking mental health services to manage anxiety and depression and the acceptability of using text messaging to communicate with a professional to receive help for managing anxiety and depression. Although the use of text messaging was not highly endorsed by African American women as an acceptable mode to converse with a professional (<50% endorsed), our prior work found that mobile video calls were viewed favorably by the majority of respondents (>70% endorsed) [22]. Concerns around privacy, confidentiality, and the impersonal feel of communicating about sensitive issues via text messages must be addressed for successful participation in text message-based interventions among this population.…”
Section: Discussionmentioning
confidence: 82%
“…Descriptive statistics were calculated for sample characteristics and responses to text messaging questions as mean, standard deviation, and range for continuous variables and as frequencies and percentages for categorical variables. As reported in prior work, age was dichotomized into 2 groups (<50 years and ≥50 years), education was categorized into 3 levels (less than bachelor's degree, bachelor's degree, and graduate degree), and response options were dichotomized as agree/somewhat agree and disagree/somewhat disagree [22]. Fisher exact test was used to determine whether an association exists between the response to each text messaging question and age group and to test for association between agreement with comfortability and perceived helpfulness of having the option to communicate with a professional through text messaging to receive help for managing anxiety and depression, respectively.…”
Section: Quantitative Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies did not report positive therapeutic outcomes following text-based counseling. Almost half of a sample of African American women reported that text-based interventions for depression and anxiety were not a desirable form of treatment [43]. A randomized controlled trial [44] showed that depression symptoms were reduced for a standard treatment with automated internet-delivered depression management more than with standard care plus optional text-based chat with a therapist.…”
Section: Limitations Of Text-based E-mental Servicesmentioning
confidence: 99%
“…It is possible that the structured format even deterred engagement. In a study of text message communication for mental health among black women, participants commonly cited an impersonal feel and inadequate communication as barriers to adoption [ 30 ], and restrictive automated communication may contribute to similar sentiments in this cohort. In comparison with other communication style clusters, the student group tended to skew older and were randomized more frequently without the social support group, which may have affected their behavior.…”
Section: Discussionmentioning
confidence: 99%